AEON.py: Python library for attractor analysis in asynchronous Boolean networks - Beneš, Nikola; Brim, Luboš; Huvar, Ondřej; Pastva, Samuel; Šafránek, David; Šmijáková, Eva (Bioinformatics (Oxford, England), 2022)
SUMMARY: AEON.py is a Python library for the analysis of the long-term behaviour in very large asynchronous Boolean networks. It provides significant computational improvements over the state-of-the-art methods for attractor detection. Furthermore, it admits the analysis of partially specified Boolean networks with uncertain update functions. It also includes techniques for identifying viable source-target control strategies and the assessment of their robustness with respect to parameter perturbations. AVAILABILITY AND IMPLEMENTATION: All relevant results are available in Supplementary Materials. The tool is accessible through https://github.com/sybila/biodivine-aeon-py. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Gene Library; Software; genová knihovna; software